Activation of muscarinic acetylcholine receptor 1 promotes invasion of hepatocellular carcinoma by inducing epithelial-mesenchymal transition. Issue 9 (October 2020) - Zhang, Liang; Wu, Li-Li; Huan, Hong-Bo; Wen, Xu-Dong; Yang, Da-Peng; Chen, Dong-Feng; Xia, Feng
Abstract : Hepatocellular carcinoma is the second leading cause of cancer-related death worldwide. Neural regulation plays an important role in the development of hepatocellular carcinoma, and activation of sympathetic nervous system can promote the migration and invasion of cancer cells. However, little research has been conducted on how the vagus nerve influences hepatocellular carcinoma. In this study, we found that the expression of vesicular acetylcholine transporter, a biomarker of vagus nerve, was associated with hepatocellular carcinoma patients' clinicopathological characteristics by immunohistochemistry. Further, activation of muscarinic acetylcholine receptor 1 (M1R) promoted HepG2 and SMMC-7721 cells migration and invasion and epithelial-mesenchymal transition via PI3K/Akt pathway. Moreover, inhibition of M1R by antagonist or shRNA suppressed hepatocellular carcinoma cells migration and invasion in vitro and in vivo, inhibited epithelial-mesenchymal transition and PI3K/Akt pathway. Therefore, these results indicate that activation of M1R promotes invasion of hepatocellular carcinoma through epithelial-mesenchymal transition and PI3K/Akt pathway. Abstract : Supplemental Digital Content is available in the text.